USING EXPERT METHODS IN THE SYSTEM OF SOLID DOMESTIC WASTE MANAGEMENT IN THE REGION - Pysarenko, P.V.; Samoilik, M.S.; Dychenko, O.Yu.; Dobrovolska, Yu. V.; Hubcheko, O.M. (Scientific Progress & Innovations, 2019)
Considering the effectiveness of recycling, first of all, it is necessary to pay attention to the following questions in the sphere of resource preservation: the effectiveness of resource using and prevising the envi-ronmental pollution. Yearly, about 480 thousand tons (1.6 million m3) of solid domestic wastes are formed in Poltava region, and they are disposed at 377 authorized disposal fields and dumping grounds, and 4.5 million tons of industrial wastes (200 thousand tons of them are dangerous wastes. The average level of using wastes as secondary resources in industry makes about one third (about 30 %) and domestic wastes – about 8 % of the total amount. Ferrous and non-ferrous metal wastes, high-grade waste paper, clean textile, polymer and wood wastes, waste glass are mainly used in economic turnover. The assessment of efficiency of solid domestic wastes’ recycling process in Poltava region was conducted. It has been established that, first of all, the following obstacles are on the way of using wastes as secondary material resources: insufficiency and imperfection of regulatory-legal framewor in the sphere of dealing with production and consumption wastes; the absence of sufficient economic stimuli for collecting and processing considerable amounts of wastes; imperfection of regulating instruments in this sector; drawbacks in the practice of collecting and disposing solid domestic wastes, which do not ensure selective collection of resource valuable fractions, suitable for repeated using; insufficient participation of the small and medium-size business in the activity connected with collecting and recycling secondary resources; imperfection of the infrastructure of collecting and recycling industrial products, which left the final using; insufficient informing business circles about the possibilities, prospects and economic attractiveness in using secondary resources. Taking into account in-vestment insufficiency, which can be directed at conducting work connected with recycling solid domestic wastes in the regions, universal scoring methods of estimating the efficiency of domestic wastes’ recycling technologies was developed. The methods will assist in selecting innovation-investment projects according to their economic and ecological importance for two cases: in the first case – for commercial implementation by business, and in the second case – for implementation with the Government support. In this aspect, the problems of attracting domestic wastes in economic turnover were determined, and economic-ecological efficiency of attracting domestic wastes in secondary consumption as a factor of resource preservation in a separate region, namely, Poltava region was substantiated.